Supremasi Hukum Pidana Militer Terhadap Anggota TNI Yang Terjerat Nestapa - Raka Tiza (Jurnal Hukum dan Sosial Politik, 2023)
Legal reform and the supremacy of military criminal law is seen as an effort to reform and supremacy of the legal system. In fact, it is a big problem for the Indonesian people to reform and enforce the law. Efforts to reform the Criminal Code have been going on for a long time, at least around 1964, but progress has been very slow. The renewal of the military criminal law is not only synonymous with the renewal of the KUHPM. Reforming the War Crimes Law is clearly more effective than simply updating the KUHPM. Renewal of military criminal law includes reform of the structure and content of the law. Renewal of military criminal law must be general in nature and renew the entire formulation of the Criminal Procedure Code, formulating it in a codification that is different from the codification of the Criminal Code. Therefore, the law must be applied as fairly as possible without being selective in imposing punishment.